Dismantling Immunosuppression in Colorectal Cancer: A Systematic Review and Meta-Analysis on Phyllanthus niruri as a Potent Antagonist of the IL-10 Axis in the Tumor Microenvironment - Jeffrey Eka Wijaya; Albertus Ari Adrianto; Awal Prasetyo (HM Publisher, 2025)
Background: The immunosuppressive tumor microenvironment (TME) of colorectal cancer (CRC), orchestrated largely by Interleukin-10 (IL-10), presents a formidable barrier to effective anti-tumor immunity. Phytochemicals from traditional medicines offer a promising avenue for immunomodulation. Phyllanthus niruri, a plant with a long history in herbal medicine, has demonstrated significant immunomodulatory potential. This systematic review aims to synthesize and critically evaluate the evidence regarding the efficacy of P. niruri and its bioactive compounds in modulating the IL-10-mediated immunosuppressive axis in CRC. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, and Google Scholar for studies published between January 2015 and August 2025. The review included in vitro, in vivo, and clinical studies investigating the effect of P. niruri on IL-10 expression and associated immune responses in CRC models. The PRISMA guidelines were followed. Study quality was assessed using SYRCLE's risk of bias tool for animal studies and the RoB 2 tool for clinical trials. A meta-analysis of IL-10 concentration data from preclinical models was performed using a random-effects model. Results: From an initial 874 records, seven studies met the inclusion criteria: three in vitro, three in vivo, and one early-phase clinical trial. The selected studies consistently demonstrated that P. niruri extracts and its lignan, phyllanthin, significantly reduced IL-10 production in CRC cell lines, tumor tissues, and patient serum. Based on three preclinical studies, a meta-analysis revealed a significant standardized mean difference (SMD) in IL-10 reduction (SMD = -2.45; 95% CI: -3.10, -1.80; p < 0.00001). This IL-10 downregulation was correlated with a significant increase in cytotoxic T lymphocyte (CD8+) infiltration, repolarization of M2 to M1 macrophages, and enhanced expression of pro-inflammatory cytokines such as IFN-γ and TNF-α. Mechanistically, P. niruri was shown to inhibit the STAT3 and NF-κB signaling pathways, key regulators of IL-10 transcription. Conclusion: While based on a limited but consistent body of evidence, our findings strongly support the role of Phyllanthus niruri as a potent modulator of the CRC immunosuppressive microenvironment by specifically targeting the IL-10 signaling axis. By reducing IL-10 production, P. niruri unleashes anti-tumor immunity, suggesting its potential as an adjuvant therapy to enhance the efficacy of conventional treatments and immunotherapies in CRC. Rigorous, large-scale clinical trials are warranted to translate these preclinical findings into clinical practice.